Comprehensive Analysis of CRIP1 Expression in Acute Myeloid Leukemia - Gao, Yan; Li, Jin-Yuan; Mao, Jia-Ying; Zhou, Jia-Fan; Jiang, Lu; Li, Xue-Ping (Frontiers in Genetics, 2022)
Acute myeloid leukemia (AML) is a highly heterogeneous hematological malignancy that faces great challenges of drug resistance and relapse. Previous studies had revealed the heterogeneous leukemia cells and the relevant gene markers CRIP1 as clinically prognostic in t(8;21)AML patients. So far, the expression and role of CRIP1 in AML is poorly understood. We used the single-cell RNA-sequencing, gene expression data from t(8;21)AML patients to analyze the immune as well as the regulation network of CRIP1. Two independent cohorts from GSE37642 and TCGA dataset served as validation cohorts. In addition, the methylation data from TCGA was used to analyze the methylation effect of CRIP1 expression. Gene expression profile from t(8;21)AML patients showed that the CRIP1-high group has an enrichment of immune related pathway including the TNFα signaling via the NFκB pathways. Further studies with the CIBERSORT showed that CRIP1-high group had a significantly higher infiltration of exhausted T cells CD8 and Mast cells activated. The expression of CRIP1 was validated in GSE37642-GPL96, GSE37642-GPL570 and TCGA datasets. In addition, with the methylation data, four CpG islands of CRIP1 (ie, cg07065217, cg04411625, cg25682097 and 11763800) were identified to be negatively associated with CRIP1 gene expression in AML patients. Our data provide a comprehensive overview of the regulation of CRIP1 expression in AML patients. The evaluation of the TNFα-NFκB signaling pathway as well as the immune heterogeneity might provide new insights for exploring improvement in AML treatment.